2022
DOI: 10.1186/s13578-022-00770-1
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 NSP13 helicase suppresses interferon signaling by perturbing JAK1 phosphorylation of STAT1

Abstract: Background SARS-CoV-2 is the causative agent of COVID-19. Overproduction and release of proinflammatory cytokines are the underlying cause of severe COVID-19. Treatment of this condition with JAK inhibitors is a double-edged sword, which might result in the suppression of proinflammatory cytokine storm and the concurrent enhancement of viral infection, since JAK signaling is essential for host antiviral response. Improving the current JAK inhibitor therapy requires a detailed molecular analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 53 publications
1
27
0
1
Order By: Relevance
“…Notably, in both superficial and suprabasal conjunctival epithelial cells, there was some evidence of suppression of paracrine type I and III IFN signaling (Figures 6B and 6C), extending recently published findings (Xia et al, 2020;Park and Iwasaki, 2020;Fung et al, 2021;Decker, 2021), suggestive of viral evasion of IFN signaling in bystander cells. It is not clear whether this is due to a paracrine effect of SARS-CoV-2 itself or an indirect consequence of other host signals, such as TNF, which is recognized to suppress IFN responses in certain contexts (Banchereau et al, 2004).…”
Section: Robust Paracrine Signaling In Response To Sars-cov-2 Infectionsupporting
confidence: 87%
“…Notably, in both superficial and suprabasal conjunctival epithelial cells, there was some evidence of suppression of paracrine type I and III IFN signaling (Figures 6B and 6C), extending recently published findings (Xia et al, 2020;Park and Iwasaki, 2020;Fung et al, 2021;Decker, 2021), suggestive of viral evasion of IFN signaling in bystander cells. It is not clear whether this is due to a paracrine effect of SARS-CoV-2 itself or an indirect consequence of other host signals, such as TNF, which is recognized to suppress IFN responses in certain contexts (Banchereau et al, 2004).…”
Section: Robust Paracrine Signaling In Response To Sars-cov-2 Infectionsupporting
confidence: 87%
“…SARS-CoV-2 Nsp14 induces lysosomal degradation of IFNAR1, an essential receptor for type I IFN, thereby preventing the activation of STAT transcription factors [ 37 ]. SARS-CoV-2 Nsp13 interacts with STAT1 to prevent JAK1-induced STAT1 phosphorylation [ 48 , 49 ]. Our assays revealed that IBV Nsp14 interacted with chJAK1 to reduce chJAK1 protein levels, but not the gene levels.…”
Section: Discussionmentioning
confidence: 99%
“…By disrupting protein trafficking, these two nsps affect cytokine secretion and MHC-I recycling and induce significant reduction of the immune response [ 76 ]. The nsp13 protein block the phosphorylation of transcription factor STAT1 [ 116 ]. Nsp14 inhibits IFNs signaling differently by facilitating lysosomal degradation of the essential interferon receptor IFNAR1.…”
Section: Host-virus Arms Racementioning
confidence: 99%